Islamic Education As An Instrument of Family Law In Strengthening Family Economic Resilience: A Maqāṣid al-Sharī‘ah Analysis of The Free Nutritious Meal Program - Eneng Humaeroh; Syifa Awalia; Endang Madali; Muhammad Bin Omar; Siti Mayang Sari (Universitas Muhammadiyah Bandung, 2025)
This study examines the role of transformative Islamic education in strengthening family economic resilience within the implementation of Indonesia’s Free Nutritious Meal Program (MBG) through the integrated perspectives of maqāṣid al-sharī‘ah and welfare-state theory. The research is motivated by persistent national challenges, including a 21.5% stunting rate, unequal access to nutrition and caregiving, and the predominantly normative orientation of Islamic Religious Education (PAI), which remains insufficiently connected to family socio-economic development. Employing a mixed-methods approach with a sequential explanatory design, the quantitative phase analyzes family economic resilience, the internalization of Islamic values, and the effectiveness of MBG implementation, while the qualitative phase explores value interpretation, educational transformation, and contextual adaptation. The study was conducted in Aceh, West Java, and West Nusa Tenggara to capture socio-cultural and institutional diversity. The findings reveal a significant gap between ritual religiosity and economic resilience, indicating that Islamic values contribute to family welfare primarily when operationalized through ḥifẓ al-māl. The MBG program contributes directly to ḥifẓ al-nafs and indirectly to ḥifẓ al-nasl; however, its long-term effectiveness remains limited without integration with value-based educational strategies and family empowerment. Transformative Islamic education enables families to move from passive welfare recipients to active economic agents by internalizing the values of justice, trustworthiness, and mutual assistance. The study contributes theoretically by proposing the Maqāṣid-Based Family Welfare Model (MBFW Model), which reconceptualizes Islamic education as a normative instrument of Islamic family law and integrates educational transformation, family economic resilience, and welfare policy within a unified framework for sustainable family development in contemporary Muslim societies.